Traduções experienciais da Urbanidade - Rheingantz, Paulo Afonso (Centro de Letras e Artes, 2020)
This article offers a reflection on the meaning of Urbanity under the principles of Actor-Network Theory (ANT) and framing it while Scientific speech. The ANT makes possible to translate the world as a net configured by the overlap of a dynamic and heterogeneous set of experiences or flows and not determined possibilities. Differently of relate and representation, translation has meant linguistic, figured and it implies in displacement of a place for another one, as well as interpretation and understanding. To translate is to make a connection to bind at and it assumes perception, as well as interpretation and appropriation. Urbanity can be translated as a collective one that results of the relations and interactions between human beings and nonhuman beings whose agreement depends on the existential context of our experiences. Based on the ANT, in place to define or to explain Urbanity, I consider to translate it as a collective one that it results of the relations and interactions between human beings and non-human beings, whose agreement depends on the existential context of our experiences. All urban collective endowed or not with Urbanity, congregates the human materiality of its physical space and elements that inhabit them, its values, affections and emotions. While some cities and places in move them, others causes malaise. These feelings or translations of Urbanity if reveal the relations between the diverse human actants and non-human actants presents in the cities and places and cannot be completely or faithful translated by words. The feeling of Urbanity contains (but it is not limited in) the materiality of a place and it does not have to be understood as a molding conceived exclusively by the human beings. The nature of the Urbanity results of the relation between nature - the world of the things in itself - and society - the world of the men in itself. The relations of Urbanity had appeared with the urbanization and precede urbanism and its theories. Urbanity can be understood as a set of narratives to be translated in its dynamic complexity. In place of the great history and a single narrative, Urbanity implies to assemble and cultivate multiple minor narratives which remain cohesive as one fiber fabric or a multiple but common tissue. Urbanity implies in the production of decentralized and not singular forms of being and knowing. Urbanity can be translated as a common world that will continue to exist independently of what the architects say or think.